Mitochondrial DNA copy number in cervical exfoliated cells and risk of cervical cancer among HPV-positive women - Wei Sun; Xueyun Qin; Jing Zhou; Mingjing Xu; Zhangyan Lyu; Xin Li; Kai Zhang; Min Dai; Ni Li; Dong Hang (BMC, 2020)
Abstract Background Although human papillomavirus (HPV) infection has been regarded as the cause of cervical cancer in over 99% of cases, only a small fraction of HPV-infected women develop this malignancy. Emerging evidence suggests that alterations of mitochondrial DNA copy number (mtCN) may contribute to carcinogenesis. However, the relationship between mtCN and cervical cancer remains undetermined. Methods The current study included 591 cervical cancer cases and 373 cancer-free controls, all of whom were infected with high-risk HPV. Relative mtCN in cervical cancer exfoliated cells was measured by qRT-PCR assays, and logistic regression analysis was performed to compute odds ratios (ORs) and 95% confidence intervals (CIs). Interaction between mtCN and HPV types was assessed by using the Wald test in logistic regression models. Results HPV16, 18, 52, and 58 were the most common types in both case and control groups. Median mtCN in cases was significantly higher than that in controls (1.63 vs. 1.23, P = 0.03). After adjustment for age and HPV types, the highest quartile of mtCN was associated with increased odds of having cervical cancer (OR = 1.77, 95% CI = 1.19, 2.62; P < 0.01), as compared to the lowest quartile. A dose-response effect of mtCN on cervical cancer was also observed (P trend < 0.001). The interaction between mtCN and HPV types was statistically nonsignificant. Conclusions In women who test HPV positive, the increase of mtCN in cervical exfoliated cells is associated with cervical cancer. This suggests a potential role of mtCN in cervical carcinogenesis.